ANALISIS UNJUK KERJA PLTD-G 40 KW BERBAHAN BAKAR MINYAK DIESEL DAN PELET BIOMASSA (STUDI KASUS DI PT INDONESIA POWER BALI) - Fransisca Sarumpaet, Yohana; Satya Kumara, I Nyoman; Ariastina, Wayan Gede (Jurnal SPEKTRUM; Vol 7 No 4 (2020): Jurnal SPEKTRUM, 2020)
Fossil-fueled power plants are still the world’s backbone in terms of electricity generation, including in Indonesia. This will continue to increase due to the high demand of electricity. Meanwhile, the amount of fossil fuels is limited and fossil fuel creates exhaust emissions. Therefore, it is required to look for clean and renewable electricity generation methods. The development of Diesel Gasifier Power Plant carried out by PT Indonesia Power Bali aims to reduce the use of diesel by using syngas obtained from gasification of biomass pellets. This study analyzes the performance of the Diesel Gasifier Power Plant at PT Indonesia Power Bali. The results show that the use of syngas reduces the use of diesel, this is indicated by the fuel consumption ratio between diesel and syngas, which is 56% diesel and 44% syngas. The results also show that the Diesel Gasifier Power Plant has an efficiency of 63% and a capacity factor of 58%.